Development of production and the influence of regional factors on technological parameters qualities of sunflower seeds and oil - M. I. Lukinykh; E. Yu. Minnikhanova; A. V. Vyatkin (Современная наука и инновации)
The article presents the results of statistics and dynamics of sunflower production for the period 1940-2020 in Russia. A correlation and regression analysis of the relationship between the indicators of sunflower seed production in the Russian Federation and a number of related data for the period 1945-2020 was performed. The analysis of the structure of production and consumption of sunflower oil in the Russian Federation is given. The purpose of the study is to study the stages of production development and the influence of regional factors on the technological parameters of the quality of sunflower seeds and oil. It is shown that the yield of sunflower seeds in most cases strongly influenced the gross harvest of sunflower seeds, while the correlation coefficient exceeded 0.7. With the exception of the period when 2.1-4.0 million tons of sunflower seeds were obtained, which may be due in some cases to adverse weather conditions and violations of cultivation technologies. The oil content in sunflower seeds depends on its content in the kernel and the amount of husk. The higher the oil content in the kernel and the lower the percentage of husk, the sunflower seeds have a rich oil content. The density of crops also affects the oil content of sunflower. Dense sowing, within certain climatic and weather conditions, contributes to an increase in the oil content in seeds. The health benefits and nutritional value of sunflower oil are due to its fatty acid composition, namely the content of unsaturated fatty acids. The content of fatty acids in various varieties of sunflower oil, including from the raw materials of the Ural region, the nutritional value of vegetable oil, the prospects for the production of vegetable oil in the Russian Federation were studied. The study of the fatty acid composition of vegetable oils was carried out on the basis of the Unified Laboratory Complex of the Ural State University of Economics. The quality assessment was carried out by chromatographic method using generally accepted techniques. It was found that the content of unsaturated fatty acids in triglycerides exceeded the content of saturated acids. Thus, for polyunsaturated fatty acids, sunflower oil of direct extraction (88.80% by weight) has a higher content, while unrefined sunflower oil has a slight deviation (88.72% by weight), flaxseed (88.49% by weight), which characterizes a high nutritional value. Thus, according to the content of linolenic acid, the highest content (61.10% by weight) was found in sunflower oil of direct extraction. Rapeseed oil is inferior to other types of oil in terms of unsaturated fatty acids (76.42% by weight). The problem of raw material quality depends on many factors, namely humidity, oil content, acidity of seeds plays an important role here. Yield depends on weather conditions, availability of zoned varieties, agrotechnical techniques. Sunflower cultivation in the Urals has its own peculiarities related to the climate and soil conditions of the region. Therefore, in order to obtain a high yield, it is necessary to choose specially adapted varieties of this crop.